Pickering foam stabilized by diacylglycerol-based solid lipid nanoparticles: effect of protein modification - Chen, Dechu; Lee, Yee Ying; Tan, Chin Ping; Wang, Yong; Qiu, Chaoying (American Chemical Society, 2024)
Pickering foams have great potential for applications in aerated foods, but their foaming ability and physical stability are still far from satisfactory. Herein, solid lipid particles (SLNs) were fabricated by using diacylglycerol of varying acyl chain lengths with modification by a protein. The SLNs showed different crystal polymorphisms and air-water interfacial activity. C14-DAG SLN with a contact angle ∼ 79° formed aqueous foam with supreme stability and high plasticity. Whey protein isolate and sodium caseinate (0.1 wt %) considerably enhanced the foamability and interfacial activity of SLNs and promoted the packing of particles at the bubble surface. However, high protein concentration caused foam destruction due to the competitive adsorption effect. β-sheet increased in protein after adsorption and changed the polymorphism and thermodynamic properties of SLN. The foam collapsing behaviors varied in the presence of protein. The results gave insights into fabricating ultrastable aqueous foams by using high-melting DAG particles. The obtained foams demonstrated good temperature sensitivity and plasticity, which showed promising application prospects in the food and cosmetic fields.